Needs assessment on discipline policy implementation by staff at the after-school-club program - Knoll, Claire (My University, 2011)
This study examined if there is a need for change in the training or implementation of the After-School Club (ASC) summer program's discipline policy by staff members, and to assess parent satisfaction with the ASC program. The staff members, program coordinator, students (grades K-5), and parents were participants in this study. Staff members received written materials and verbal training from the program coordinator prior to the start of the summer session. Measurement of staff self-efficacy beliefs concerning management of children's behavior, implementation of effective management procedures, level of compliance with the behavior policy (i.e., observed on-taskloff-task behavior), understanding of the ASC behavior policy, and reported responses to coinmon situations was collected. Measurement of the program coordinator's understanding of the ASC behavior policy and reported staff responses to common situations was also collected. Additionally, measurement of student understanding of the ASC behavior policy, reported staffresponses to common situations, and student engagement was collected. Lastly, measurement of parent satisfaction with the ASC program's discipline policy was collected. Results indicated that there is a need for change in the implementation of the discipline policy by staff. This could be achieved through additional staff training and targeted recruiting for staff members. Results also indicated that overall parents are very satisfied with the ASC program; however these findings were limited due to minimal parent response. Overall, this study provides a comprehensive look at discipline policy implementation by staff and makes recommendations to improve current practices.
Keywords: School discipline; After-school programs